A novel urodynamic model for lower urinary tract assessment in awake rats. (April 2015) - Schneider, Marc P.; Hughes, Francis M.; Engmann, Anne K.; Purves, J. Todd; Kasper, Hansjörg; Tedaldi, Marco; Spruill, Laura S.; Gullo, Miriam; Schwab, Martin E.; Kessler, Thomas M.
Abstract : Objectives: To develop a urodynamic model incorporating external urethral sphincter (EUS) electromyography (EMG) in awake rats. Materials and Methods: Bladder catheters and EUS EMG electrodes were implanted in female Sprague Dawley rats. Assessments were performed in awake, lightly restrained rats on postoperative day 12–14. Measurements were repeated in the same rat on day 16 under urethane anaesthesia. Urodynamics and EUS EMG were performed simultaneously. In addition, serum creatinine and bladder histology was assessed. Results: No significant differences in urodynamic parameters were found between bladder catheter only vs bladder catheter and EUS EMG electrode groups. Urethane anaesthesia evoked prominent changes in both urodynamic parameters and EUS EMG. Serum creatinine was within the normal limits in all rats. Bladder weight and bladder wall thickness were significantly increased in both the bladder catheter only and the bladder catheter and EUS EMG group compared with controls. Conclusions: Our novel urodynamic model allows repetitive measurements of both bladder and EUS function at different time points in the same rat under fully awake conditions and opens promising avenues to investigate lower urinary tract dysfunction in a translational approach.